2003
DOI: 10.1002/cvde.200304153
|View full text |Cite
|
Sign up to set email alerts
|

Growth of IrO2 Films and Nanorods by Means of CVD: An Example of Compositional and Morphological Control of Nanostructures

Abstract: was evaluated over a circular area measuring roughly 500 lm in diameter [13]. After deposition, each of the samples was inspected using an optical stereomicroscope and a scanning electron microscope (SEM) equipped with an energy-dispersive spectrometer. Growth of IrO 2 Films and Nanorods by Means of CVD: An Example of Compositional and Morphological Control of Nanostructures**By Reui-San Chen, Yi-Sin Chen, Ying-Sheng Huang,* Yao-Lun Chen, Yun Chi, Chao-Shiuan Liu, Kwong-Kau Tiong, and Arthur J. Carty Iridium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…This preliminary result indicates that such low-pressure reaction conditions are highly effective for inducing clean conversion to iridium metal. [17] XRD analysis confirmed the polycrystalline nature of the deposited material by showing a statistical distribution of both (111) and (200) diffraction signals expected for the bulk iridium metal (Fig. 5).…”
supporting
confidence: 73%
“…This preliminary result indicates that such low-pressure reaction conditions are highly effective for inducing clean conversion to iridium metal. [17] XRD analysis confirmed the polycrystalline nature of the deposited material by showing a statistical distribution of both (111) and (200) diffraction signals expected for the bulk iridium metal (Fig. 5).…”
supporting
confidence: 73%
“…This additional shift has been attributed to the residual stress effect induced by tensile strain. 19 Rosenblum et al 15 reported the observation of a blueshift of the three strongest lines induced by hydrostatic pressure in 24 The first investigation of the Raman scattering of IrO 2 NCs was by Chen et al 20 The samples were grown via the MOCVD technique at temperatures in range of 300-450°C, which exhibited randomly oriented, vertically aligned nanorods (NRs). The average length and radius of these IrO 2 NRs were estimated to be 3.5 š 0.2 µm and 150 š 50 nm, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, such a nanosized IrO 2 tip has been realized using metalorganic chemical vapor deposition (MOCVD) technique [14]. In this report, a detailed characterization for the IrO 2 nanorods grown on Si(1 0 0) substrate are carried out.…”
Section: Introductionmentioning
confidence: 99%